Who were the accused witches of Salem? : and other questions about the witchcraft trials - Waxman, Laura Hamilton (Six questions of American history., 2012)
Explores what primed Salem for its witchcraft fever, key people in the drama, and the events of the Salem witch trials that led to the execution of 19 innocent people.